Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.